2008
DOI: 10.1159/000177036
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Respiratory Infections in ‘Nil by Mouth’ Tube-Fed Acute Ischemic Stroke Patients

Abstract: Background: Respiratory infections are common in acute stroke. Previous studies have found dysphagia is associated with respiratory infections. Of interest is whether patients who are ‘Nil by Mouth’ (NBM) and tube fed have higher risk of developing infections due to aspiration of bacteria-laden saliva or refluxed material than stroke patients who are fed orally. Methods: Prospective cohort of 330 ischemic stroke survivors were followed for 30 days and infections recorded. Results: 115 infections were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 60 publications
6
69
0
4
Order By: Relevance
“…[9][10][11] Evidence that NGT placement increases PSP incidence remains equivocal; observational studies suggesting this association are limited by heterogeneity in patients, settings, and diagnostic criteria for PSP. [6][7][8] It is possible that PSP and higher mortality are influenced by stroke severity rather than by NGT placement.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11] Evidence that NGT placement increases PSP incidence remains equivocal; observational studies suggesting this association are limited by heterogeneity in patients, settings, and diagnostic criteria for PSP. [6][7][8] It is possible that PSP and higher mortality are influenced by stroke severity rather than by NGT placement.…”
Section: Resultsmentioning
confidence: 99%
“…Respiratory infection was significantly more likely to occur in patients with dysphagia (Langdon, Lee & Binns, 2007). In a cohort of 330 acute ischemic stroke patients followed up for the first month after their stroke, there were 51 respiratory infections, with dysphagia again a significant predictor of patients who developed infections (Langdon, Lee & Binns, 2009). …”
Section: High Early Incidence Of Dysphagia Its Causes Presentation mentioning
confidence: 99%
“…They found that the bacteria in the respiratory samples and those found in plaque were the same (El-Solh, Pietrantoni, Okada, Bhat, Zambon, Aquilina, and Berbery, 2004). Stringent oral care and strategies to minimize reflux in the acute stroke population has the potential to reduce respiratory infections (Langdon, Lee & Binns, 2009). …”
Section: Oral Hygienementioning
confidence: 99%
See 1 more Smart Citation
“…Kommentar: Es gibt einige Hinweise, dass die Rate an Atemwegsinfekten bei sondenernährten dysphagischen Schlaganfallpatienten höher ist als bei oral ernährten Patienten [9,106]. Es kann jedoch davon ausgegangen werden, dass dies in den meisten Fällen am höheren Schweregrad der Dysphagie liegt, die der Grund für die Sondenernährung ist.…”
Section: Welche Methoden Sollten Für Dasunclassified